2015
DOI: 10.1158/1055-9965.epi-15-0305
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Disparity in Symptomatic Breast Cancer Awareness despite a Recent Screen: The Role of Tumor Biology and Mammography Facility Characteristics

Abstract: BACKGROUND In a racially and ethnically diverse sample of recently diagnosed urban breast cancer patients, we examined associations of patient, tumor biology and mammography facility characteristics on the probability of symptomatic discovery of their breast cancer despite a recent prior screening mammogram. METHODS In the Breast Cancer Care in Chicago study, self-reports at interview were used to define patients as having a screen-detected breast cancer or having symptomatic awareness despite a recent scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 40 publications
3
10
0
Order By: Relevance
“…4-8; i.e., triple-negative basal-like) in women of west African descent (9)(10)(11)(12). Overall, women of African descent are more likely to be diagnosed with the worst types of breast cancer, including triple-negative breast cancer (TNBC), at earlier ages with the poorest prognosis indications (8,10,(13)(14)(15), despite having access to proper screening and standard treatments (16). There is a clear need to better understand how the molecular dynamics of tumor progression may differ among women of African descent, compared with women of European descent.…”
Section: Introductionmentioning
confidence: 99%
“…4-8; i.e., triple-negative basal-like) in women of west African descent (9)(10)(11)(12). Overall, women of African descent are more likely to be diagnosed with the worst types of breast cancer, including triple-negative breast cancer (TNBC), at earlier ages with the poorest prognosis indications (8,10,(13)(14)(15), despite having access to proper screening and standard treatments (16). There is a clear need to better understand how the molecular dynamics of tumor progression may differ among women of African descent, compared with women of European descent.…”
Section: Introductionmentioning
confidence: 99%
“…The Breast Cancer Care in Chicago study was approved by the Institutional Review Board at the University of Illinois at Chicago, and has been described elsewhere [20, 28]. This population-based study performed case finding at all 56 diagnosing facilities in the greater Chicago area that diagnosed patients who were Chicago residents at diagnosis.…”
Section: Methodsmentioning
confidence: 99%
“…This fact can be seen in studies of survival in patients diagnosed with breast cancer [13] and from population-based studies that show a corresponding disparity in breast cancer mortality rates within the U.S. population [1, 46]. There are many potential explanations for the disparity, including differences in the quality of and access to breast cancer care [715], as well as differences in the incidence of aggressive breast cancer subtypes in black versus white patients [2, 10, 16–20]. Particular emphasis has been placed on the increased incidence of triple negative (TN) breast cancers, which lack targetable hormone and growth factor receptors, in black women as a major driver of outcome disparities [21].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to having more aggressive tumors, nL Black women also appear to be less likely to have access to the highest quality breast cancer screenings, according to studies of mammography access and quality conducted in Chicago (915). A recent analysis from the population-based Breast Cancer Care in Chicago study revealed that nL Black breast cancer patients were more likely than their nL White counterparts to report symptomatic awareness of their breast cancer despite a recent screening mammogram (10). For these reasons, it would be reasonable to expect an excess diagnosis of IBC among nL black women.…”
Section: Introductionmentioning
confidence: 99%